Internalization of therapeutic antibodies into dendritic cells as a risk factor for immunogenicity - Siegel, Michel; Bolender, Anna-Lena; Ducret, Axel; Fraidling, Johannes; Hartman, Katharina; Looney, Cary M.; Rohr, Olivier; Hickling, Timothy P.; Kettenberger, Hubert; Lechmann, Martin; Marban-Doran, Céline; Kraft, Thomas E. (Frontiers in Immunology, 2024)
Immunogenicity, defined as the unwanted immune response triggered by the administration of therapeutic antibodies, leads to the production of anti-drug antibodies and is a significant risk factor for the development of therapeutic antibodies. Immunogenicity is a multifactorial phenomenon and risk factors influencing each and every step of the immune response may have major overall consequences. Previously, it has been observed that biophysical properties such as positive charge patches affect the biodistribution of therapeutic antibodies, pharmacokinetic properties like nonspecific clearance by altering their uptake into endothelial cells. The internalization of therapeutic antibodies into dendritic cells plays a crucial role in immunogenicity. Cellular internalization is mainly facilitated by nonspecific endocytosis or fluid phase pinocytosis. It involves the cell engulfing surrounding fluid, leading to the internalization of its contents. The biophysical properties of therapeutic antibodies, such as positive charge patches, can influence this process as described for endothelial cells. We therefore hypothesize that internalization of therapeutic antibodies into dendritic cells is influenced by their biophysical properties. Investigating the link between charge patches and dendritic cells internalization using tool antibodies with large positive or negative charge patches, we observed that antibodies with large positive charge patches showed higher lysosomal accumulation and epitope presentation, an important risk factor for immunogenicity. To understand the subsequent impact on T cell activation, we inserted a CD4+ T cell epitope from ovalbumin (a model antigen with well-characterized T cell epitopes) into the same tool compounds. This insertion led to no significant changes in dendritic cell internalization or T cell epitope presentation compared to wild-type antibodies, allowing for a direct comparison of the impact of internalization T cell epitope presentation on T cell activation. However, the insertion of the ovalbumin CD4+ T cell epitope into the tool antibodies increased the occurrence of a specific T cell response, coupled with enhanced internalization and epitope presentation. This increased activation is a key risk factor in immunogenicity, emphasizing the need for careful consideration during the development of biotherapeutics. In conclusion, positive charge patches-mediated internalization and presentation significantly influence the immunogenicity of therapeutic antibodies.